Computed tomographic detection of a swallowed denture - McLaughlin, M G; Swayne, L C; Caruana, V (Computerized medical imaging and graphics, 1989)
A 89-year-old, nursing home female presented with a two-week history of drooling and a hard palpable mass in the region of the larynx. Initial fiberoptic laryngoscopy revealed a hard pinkish-white mass which was felt to represent a tumor. Computed tomography demonstrated swallowed, impacted, complete, mandibular denture. Radiologists should be aware of this problem, particularly in the elderly demented patient.